Knowledge and Attitude Students Through Nutrition Health Education with E-Modul “Against Stunting” - Adriyani Adam; Aswita Amir; Dinul Islam; Ali Imran (Indonesian Journal of Global Health Research, 2022)
Stunting in Indonesia is a very serious problem because the percentage is above form cut off point of World Health Organization is only 20%. The results of South East Asia Nutritions Surveys (SEANUTS), around 24.1% of boys and 24.3% of girls in Indonesia are stunted. Based on Basic Health Research (2018), the incidence of stunting among children under five in South Sulawesi is still high, which is above 30% and South Sulawesi is the fourth highest in Indonesia. One of the preventive efforts to reduce stunting from an early age by nutrition health education through developing an electronic module about stunting as a method of nutrition health education which contains information about stunting. The purpose of this study was to determine the effect of nutrion health education on students' knowledge and attitudes through the development of the E-Module "Against Stunting" at SMU Negeri 1 Makassar City. The research method used is a Quasi Experiment, with a total sample of 64 students based on inclusion and exclusion criteria and then divided into the intervention group and the control group. Before the intervention, a pre-test was carried out on the two groups, then students in the intervention group were given nutrition education through an e-module containing knowledge about stunting, its causes and prevention continuously every week and at the end, a post test was carried out on the intervention group and the control group. The data collected were analyzed using the Man Whitney test. The results showed that there was an effect of nutrition heath education on increasing the knowledge and attitudes of students at SMU Negeri 1 Makassar City.